The bone queen - Croggon, Alison (The books of Pellinor / Alison Croggon, 2016)
Cadvan of Lirigon, one of the most brilliant Bards of his generation, has been exiled for a terrible crime that unleashed the power of the Bone Queen and wrought destruction across Annar. Meanwhile, in Lirigon, several unnerving events suggest that the Dark is growing in strength once again, and that the Bone Queen may yet lurk in the world. If he is to save both the living and the dead, Cadvan must once again face the evil that almost destroyed him